Oral candidal carriage correlates with CD4+ cell count but not with HIV and highly active antiretroviral therapy status. Issue 4 (17th July 2019) - Sah, Parul; Patel, Pratik; Chandrashekar, Chetana; Martena, Suganthi; Ballal, Mamatha; Hegde, Manjayya; Guddattu, Vasudeva; Murdoch, Craig; Sharma, Mohit; Radhakrishnan, Raghu
Abstract: Aim: The occurrence of oropharyngeal candidiasis (OPC) may be influenced by oral candidal carriage (OCC). Although OPC is strongly associated with low CD4 + cell count (400‐700 cells/mm 3 ) and a lack of highly active antiretroviral therapy (HAART), the effect of these two parameters on OCC is debatable. We investigated the oral candidal carriage, species diversity, antifungal susceptibility and the association of OCC with CD4 + cell count and HAART. Methods: Oral candidal isolates from 120 HIV + patients (60 receiving and 60 not receiving HAART) and 60 healthy controls were quantified, and their species determined using standard culture and biochemical methods, followed by antifungal susceptibility testing using the agar dilution method. Results: The OCC was significantly higher in HIV + patients; Candida albicans was the most frequently isolated species in both groups, followed by Candida tropicalis . Candidal density carriage correlated significantly with CD4 + cell count, but not with HIV and HAART status. Among the isolates from HIV + patients, 35.4% showed reduced susceptibility to fluconazole. Conclusion: HIV status results in significantly elevated rates of OCC C albicans remains the predominant pathogen, although other species are emerging rapidly. Resistance to fluconazole is on the rise, and more efficient treatment strategies need to be implemented.